Two-probe implementation of microwave interferometry for motion sensing and complex reflection coefficient measurement - Pylypenko O.V.; Doronin, A.V.; Gorev, N.B.; Kodzhespirova, I.F. (Технічна механіка, 2018)
This paper presents the results of the investigations into microwave probe measurements conducted at the Department for Functional Elements of Control Systems of the Institute of Technical Mechanics of the National Academy of Sciences of Ukraine and the State Space Agency of Ukraine over the past five years. These investigations resulted in a two-probe implementation of microwave interferometry that allows one to measure both the displacement of a mechanical object and the complex reflection coefficient of a material specimen. В данной статье приведены результаты исследований по микроволновым зондовым измерениям, которые проводились в отделе функциональных элементов систем управления Института технической механики Национальной академии наук Украины и Государственного космического агентства Украины в течение последних пяти лет. В результате этих исследований разработан двухзондовый вариант сверхвысокочастотной интерферометрии, который позволяет измерять как перемещение механического объекта, так и комплексный коэффициент отражения образца материала. У статті наведено результати досліджень з мікрохвильових зондових вимірювань, що проводилися у відділі функціональних елементів систем керування Інституту технічної механіки Національної академії наук України і Державного космічного агентства України на протязі останніх п’яти років. У результаті цих досліджень розроблено двозондовий варіант надвисокочастотної інтерферометрії, який дозволяє вимірювати як переміщення механічного об’єкта, так і комплексний коефіцієнт зразка матеріалу.